THE GAMIFICATION PYRAMID: A CONCEPTUAL FRAMEWORK FOR ADULT LEARNING AND ORGANIZATIONAL READINESS - Jovevski, Dimitar; Mijoska belshoska, Marina; Tea Josimovska (Institute for Knowledge Management, 2025)
One of the most talked-about tactics in corporate training, education, and organizational development is gamification. Gamification aims to promote desirable behaviors, maintain engagement, and encourage participation by incorporating game design elements—such as quests, challenges, leaderboards, badges, and points—into non-gaming contexts. Organizations are looking for scalable ways to improve readiness and learning outcomes, and learners and employees are already used to interactive and reward-driven systems in their everyday digital lives, which explains why gamification is being adopted quickly across sectors. However, despite its increasing popularity, gamification research is still dispersed. Current models frequently offer descriptive taxonomies of user types or motivational drivers, but they are unable to explain how gamification systems transform from superficial rewards into long-lasting frameworks that encourage sustained engagement and significant results. The literature is dominated by a few key frameworks. Eight fundamental human motivational factors are identified by Yu-kai Chou's Octalysis Framework, which also makes a distinction between positive and negative motivators and intrinsic and extrinsic drivers. A systematic viewpoint that describes how gamification components work together over time to create scalable, sustainable engagement is what's lacking; this gap is especially noticeable in programs for organizational readiness and adult learning. By presenting the Gamification Pyramid as a helpful interpretive tool that enhances rather than replaces current models, this paper fills that gap. The Pyramid divides gamification into three levels: dynamics, which stand for the emergent psychological states of mastery, trust, collaboration, and purpose that maintain motivation over time; mechanics, which arrange and link those components into meaningful pathways; and components, which offer the obvious building blocks of engagement. The benefits of this progression are particularly noticeable in organizational and adult learning settings. Adult learners who are juggling many obligations rarely pay attention to badges and points, even though they can produce temporary compliance. To show progress and relevance, strategies like feedback systems, staged challenges, and group projects are crucial. But in the end, only dynamics—the higher-order results of mastery, trust, and cooperation—can generate long-lasting motivation that complements corporate strategy and career advancement. The paper places the Pyramid in the larger context of models like Octalysis, Hexad, Werbach and Hunter's taxonomy, and Nicholson's meaningful gamification through an organized review of gamification research. This positioning is summarized in two comparative tables. The first explains the special value of a hierarchical progression lens by contrasting major frameworks based on their focus, advantages, and disadvantages. With applications ranging from compliance training and onboarding to upskilling, leadership development, and organizational transformation, the second converts these insights into useful suggestions for creating gamification in adult learning and organizational contexts.
Keywords: Adult Learning, Gamification, Motivation, Framework, Gamification Pyramid